The Physical Internet: A means towards achieving global logistics sustainability - Moshood Taofeeq D. (De Gruyter, 2021)
The supply chains that make up the distribution networks are becoming more diverse as companies respond to global markets’ rigorous demands. Today, the immediate need for sustainable growth is to design, manufacture, and deliver the right product to experience drastic improvements in the right place, at the right price, and at the right time. As a massively distributed, integrated logistics infrastructure, a new “Physical Internet” (PI) model has been implemented to make the existing logistics structures more scalable and sustainable. This article discusses resource control in the PI’s modern supply chain and logistics systems while addressing the potential disruptions between the hubs during the transfer of goods. This article attempts to establish how companies will benefit from introducing the PI to optimise their strategic supply chain. This article used ATLAS.ti 9 automated tool to save, classify, and evaluate the data for this analysis to review the literature systematically. For PI, an increasing number of plans, blueprints, and requirements have been established. Still, minimal models are currently developed, explaining how the transformation from the strengthened logistics business models to the PI could occur. There is a lack of awareness of the necessary market structures that can include crucial players and allow the PI model to be embraced. Therefore, this research brings a new viewpoint on logistic operations through the PI idea, guarantees the present situation’s view, and presents a solution to the society–business–technology framework.